Circadian Clock and Sirtuins in Diabetic Lung: A Mechanistic Perspective - Zhou, Shuang; Dai, Yi-Min; Zeng, Xiao-Feng; Chen, Hou-Zao (Frontiers in Endocrinology, 2020)
Diabetes-induced tissue injuries in target organs such as the kidney, heart, eye, liver, skin and nervous system contribute significantly to the morbidity and mortality of diabetes. However, whether the lung should be considered a diabetic target organ has been discussed for decades. Accumulating evidence shows that both pulmonary histological changes and functional abnormalities have been observed in diabetic patients, suggesting that the lung is a diabetic target organ. Mechanisms underlying diabetic lung are unclear, however, oxidative stress, systemic inflammation and premature aging convincingly contribute to them. Circadian system and Sirtuins have been well documented to play important roles in above mechanisms. Circadian rhythms are intrinsic mammalian biological oscillations with a period of near 24 hours driven by the circadian clock system. This system plays an important role in the regulation of energy metabolism, oxidative stress, inflammation, cellular proliferation and senescence, thus impacting metabolism-related diseases, chronic airway diseases and cancers. Sirtuins, a family of adenine dinucleotide (NAD+)-dependent histone deacetylases, have been demonstrated to regulate a series of physiological processes and affect diseases such as obesity, insulin resistance, type 2 diabetes (T2DM), heart disease, cancer and aging. In this review, we summarize recent advances in the understanding of the roles of the circadian clock and Sirtuins in regulating cellular processes and highlight the potential interactions of the circadian clock and Sirtuins in the context of diabetic lung.